Unique responses of the fixed stoichiometric TRPC1–TRPC5 concatemer to G proteins - Kang, Hana; So, Insuk (Frontiers in Physiology, 2024)
Transient receptor potential canonical (TRPC)5 channel is a nonselective cation channel that plays a significant role in membrane depolarization and calcium influx. TRPC5 not only forms homotetramers itself but also heterotetramers with TRPC1. However, accurately testing and confirming these heterotetrameric channels at specific ratios has proven challenging. Therefore, creating heteromeric concatemers of TRPC5 and TRPC1 with a fixed stoichiometry of 1:1 becomes essential. This study aims to meticulously identify and reaffirm the properties of TRPC5 homomers and heteromers with a 1:1 fixed stoichiometry, to determine the optimal ratio for the TRPC1/5 heterotetramer. Overall characteristics were consistent with the previous studies, but several specific features were different. The TRPC1-TRPC5 concatemer is activated by Englerin A, but neither carbachol nor constitutively active Gαi protein can trigger its activation. However, carbachol can activate the TRPC1-TRPC5 concatemer when internal GTPγS is present. Meanwhile, the TRPC5-TRPC5 concatemer is responsive to both carbachol and Englerin A. In conclusion, we provide evidence that TRPC1-TRPC5 heteromeric concatemer with fixed stoichiometry need specific condition to respond to carbachol whereas TRPC5-TRPC5 homomeric concatemer responds physiologically to carbachol. Additional research may be necessary to ascertain the optimal stoichiometry for the TRPC1-TRPC5 concatemer to enhance its electrophysiological properties.